The alloying-induced electrical conductivity of metal–chalcogenolate nanowires. Issue 70 (11th August 2021) - Ke, Feng; Zhou, Chuanjun; Zheng, Mengke; Li, Hao; Bao, Junjie; Zhu, Chen; Song, Yongbo; Xu, Wen Wu; Zhu, Manzhou
Abstract : The introduction of copper atoms significantly changes the electronic structure of the MOC nanowires and improves their electrical conductivity. Abstract : Alloying is one of the most effective strategies to change the properties of inorganic–organic hybrid materials, but there are few reports of the alloying of one-dimensional nanowires with precise atomic structure due to the difficulties in obtaining the single crystals of nanowires themselves. Herein, we describe the synthesis and characterization of an alloyed one-dimensional Ag–Cu nanowire [Ag2.5 Cu1.5 (S-Adm)4 ] n . Compared with the unalloyed [Ag4 (S-Adm)4 ] n, our novel alloyed nanowire exhibits good conductivity, and its resistivity (as a powder) was determined to be 107 Ω m by impedance analysis–consistent with that of a semiconductor. Accordingly, based on these properties combined with its excellent thermal stability and high-yielding, gram-scale synthesis, [Ag2.5 Cu1.5 (S-Adm)4 ] n is proposed for electronic-device applications.